Is glycogenic acanthosis a predictor of insulin resistance and metabolic syndrome? - Tahtacı, Mustafa; Demirezer Bolat, Aylin; Tayfur Yürekli, Öykü; Köseoğlu, Hüseyin; Başaran, Murat; Özer Sarı, Sevil; Ersoy, Osman (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: To evaluate the incidence of insulin resistance and metabolic syndrome (MetS) in patients with glycogenic acanthosis (GA). Materials and Methods: Thirty patients with GA, detected upon endoscopy, and 30 age- and sex-matched control patients without GA were included in this case-control study. Patients with GA were considered group 1 and control group was considered group 2. Anthropometric measurements [height, weight, and waist circumference (WC)], biochemical parameters [fasting plasma glucose (FPG), triglyceride, high-density lipoprotein (HDL), and low-density lipoprotein (LDL)], and serum fasting insulin levels were evaluated. Insulin resistance (IR) was estimated by the homeostatic model assessment of IR. MetS was diagnosed using the criteria of the National Cholesterol Education Program Adult Treatment Panel III. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated to evaluate associations with GA. Results: There were no differences in terms of FPG, triglyceride, HDL, and LDL between groups (p-values 0.118, 0.114, 0.192, 0.086, respectively). WC was significantly higher in group 1 than in group 2 (103.77 vs 97.03, p=0.032). The number of patients with IR and MetS were significantly higher in group 1 than in group 2 (53.3% vs 13.3%, p=0.003 and 53.3% vs 23.3%, p=0.034). ORs [95% CI] of WC, IR, and MetS for GA were 0.68 [0.17-2.62], 7.12 [1.89-26.72], and 4.11 [1.04-16.21], respectively. Conclusion: These findings showed that IR and MetS were significantly associated with the presence of GA. Cite this article as: Tahtacı M, Demirezer Bolat A, Tayfur Yürekli Ö, et al. Is glycogenic acanthosis a predictor of insulin resistance and metabolic syndrome? Turk J Gastroenterol 2017; 28: 337-41.